Red Herrings and Ethical Issues in Artificial Intelligence - John Orlando (The Pinnacle)
Discussions of the ethical issues with artificial intelligence tend to focus on red herrings such as plagiarism and bias. I argue that the real issues revolve around the extent to which humans will cede control to machines.